A high-performance cement-based composite material for repair and reinforcement engineering and preparation method thereof

By using composite cement and optimized fiber system, high-ductility concrete with large flow state, fast hard and high strength is prepared, which solves the problems of inverted strength and poor durability of repair and reinforcement engineering materials in the prior art, and realizes high-performance and durable repair and reinforcement materials.

CN119774960AActive Publication Date: 2025-04-08CNBM ZHONGYAN TECH +1

Patent Information

Application Number
CN202510287050.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-08
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

In the prior art, ultra-early-strength concrete and polymer-modified concrete used in repair and reinforcement projects will invert the strength part in the later stage, the material has poor durability and is prone to cracking, which cannot meet the requirements of rapid construction and high performance.

Method used

Compound cement, admixture, quartz sand, mixed fibers, reinforcement, nucleating agents, and toughening agents are used as the main raw materials. By improving the glue system and fiber system and optimizing the admixture composition, high-ductile concrete with large flow state, fast hardness and high strength is prepared.

Benefits of technology

The early strength and later strength of high-ductility concrete have been achieved, and the durability and toughness of the material have been significantly improved, which is suitable for rapid restoration and reinforcement projects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of cement-based building materials, and in particular to a high-performance cement-based composite material for repair and reinforcement engineering and a preparation method thereof. The present invention, on the one hand, starts from a glue system to solve the problems of low mechanical strength and slow hardening time of cement-based composite materials; on the other hand, starts from a fiber system, selects a method of modifying a variety of fibers to make the fibers easier and more uniformly dispersed in mortar, ensuring that the slurry can have relatively good working performance, and optimizes admixtures to prepare a high-ductility concrete with large fluidity, fast hardening and high strength, so that it can meet the needs of rail transit and road rapid repair and reinforcement engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a high-performance cement-based composite material for repair and reinforcement engineering and a preparation method thereof. Background Art

[0002] Economic development requires developed transportation to ensure it. With the rapid development of the transportation industry, road and rail facilities have begun to show signs of pavement wear, aging and damage due to the increase in service life and traffic volume. This will not only affect transportation efficiency, but may also pose a safety hazard.

[0003] Therefore, repair and reinforcement work becomes particularly important. At present, super-early-strength concrete or polymer-modified concrete is mostly used for emergency repairs of road surfaces, tracks, and tunnel structures. Although these products can reach high strength within a few hours and achieve the purpose of quickly restoring traffic, the strength part will shrink in the later stage, and the durability of the material is poor and prone to cracking.

[0004] As the construction industry's demand for rapid repair and reinforcement increases, traditional concrete materials, with their poor durability, weak ability to resist deformation loads, and insufficient ductility, can no longer meet the requirements of rapid construction and high performance.

[0005] High ductility concrete is a fiber-reinforced cement-based composite material with excellent ductility, high damage resistance, high durability and high strength (compression and tension).

[0006] Due to its outstanding performance, it is widely used in seismic reinforcement of building structures and repair and reinforcement of old buildings.

[0007] At present, most of the ECC materials available on the market are designed for the reinforcement of building structures, but they are rarely used in emergency repair projects. In addition, the proportion of cementitious materials such as fly ash and silica fume in the materials is relatively high, resulting in slow strength growth, low strength in the later stage, high concrete viscosity, poor working performance, and not conducive to construction. Therefore, it is particularly important to develop a high-ductility concrete material with early strength, fast hardening, and large fluidity. Summary of the invention

[0008] In order to solve the problems existing in the prior art, the present invention provides a high-performance cement-based composite material for repair and reinforcement projects, which is also a high-ductility concrete, also called a high-ductility cement-based material. Specifically, the present invention adopts compound cement, admixtures, quartz sand, mixed fibers, reinforcing agents, nucleating agents, and toughening agents as main raw materials. On the one hand, starting from the adhesive system, the problems of low mechanical strength and slow hardening time of cement-based composite materials are solved; on the other hand, starting from the fiber system, a method of modifying a variety of fibers is selected to make the fibers easier to disperse and evenly disperse in the mortar, ensuring that the slurry can have relatively good working performance, and optimizing the admixture to prepare a high-ductility concrete with large fluidity, fast hardening and high strength, so that it can meet the needs of rapid repair and reinforcement projects.

[0009] Specifically, the high-performance cement-based composite material for repair and reinforcement engineering of the present invention is composed of the following raw materials in parts by weight: 100-120 parts of compound cement, 30-60 parts of admixture, 90-120 parts of quartz sand, 1-3 parts of mixed fiber, 2-5 parts of reinforcing agent, 1-3 parts of nucleating agent, 1-2 parts of toughening agent, and 38-42 parts of water.

[0010] Preferably, the composite cement is prepared by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of (2-4):(1-4):(1-2). The present invention uses three types of cement for composite, shortens the setting time, improves the early strength, and ensures the late strength of high ductility concrete.

[0011] Preferably, the admixture is formed by mixing fly ash, mineral powder and silica fume in a mass ratio of (10-30):(8-12):(5-7).

[0012] Preferably, the hybrid fiber is formed by mixing ozone-modified PE fiber and PVA fiber in a mass ratio of 1: (0.9-1.2). The present invention modifies the PE fiber by ozone modification, so that more hydrophilic groups such as hydroxyl and carboxyl groups can be attached to the fiber surface, thereby improving the hydrophilicity and promoting the flow properties of high-ductility concrete; ozone-modified PE fiber and PVA fiber are selected and mixed in a certain proportion to produce a good hybrid effect, thereby improving the toughness and crack resistance of the concrete.

[0013] Preferably, the reinforcing agent is prepared by mixing a water reducing agent, a defoaming agent, a redispersible latex powder and an early strength agent in a mass ratio of (2-4):(1-4):(1-4):(1-2).

[0014] Preferably, the nucleating agent is a mixture of nano-SiO2, nano-CaCO3, and nano-graphene oxide in a mass ratio of (2-5):(1-3):(3-5). The present invention uses nano-SiO2 and nano-CaCO3 as inorganic nucleating agents, which are compounded with nano-graphene oxide organic nucleating agents, innovatively integrating nanotechnology to provide cement nucleation sites, so that the composite cement achieves an early strength effect in the early stage.

[0015] Preferably, the toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium raw material and dispersant in a mass ratio of (30-40):(55-75):(10-22):(3-15):(1-2.5). The present invention adds a toughening agent, which can optimize the composition of cementitious materials, regulate the composition of cement mineral phases, change the hydration reaction process of different cement mineral phases, and affect the formation rate of calcium sulfonate. In addition, the toughening agent reacts to generate a large number of self-generated large-size calcium sulfonate whiskers, and the whisker length can reach 20-50 μm, which is 2-5 times the length of calcium sulfonate hydrated by ordinary cement. The large-size calcium sulfonate whiskers can be used as micron-scale fibers, which can not only play a "bridge" role to connect various hydration products, but also fill the porous structure in the cement to make the structure denser, thereby achieving an in-situ self-toughening effect. In addition, it can realize a multi-scale fiber synergistic reinforcement effect with the hybrid fiber of the present invention, and can solve the problem of uneven dispersion of fibers in cement, thereby effectively improving the continuity of high-ductility concrete materials and achieving reinforcement and toughening.

[0016] Preferably, the strength grade of each cement in the compound cement is ≥42.5.

[0017] Preferably, the ozone-modified PE fiber preparation process is: washing and drying the PE fiber, placing it in an ozone generator for oxidation treatment, and washing and drying it again to obtain the ozone-modified PE fiber.

[0018] Preferably, the oxidation treatment temperature is 60-80°C, the ozone gas flux is 200-500 mL / min, the ozone concentration is set at 19-22 g / L, and the oxidation treatment time is 25-40 min.

[0019] Preferably, the PE fiber length is 6-18 mm.

[0020] Preferably, the water reducer is a polycarboxylic acid water reducer, the defoamer is an organosilicon defoamer, and the early strength agent is at least one of tartaric acid, lithium carbonate, and sodium nitrite.

[0021] Preferably, the gypsum is at least one of anhydrite, dihydrate gypsum and hemihydrate gypsum, the calcium raw material is at least one of calcium oxide, quicklime and slaked lime, and the dispersant is at least one of sodium tripolyphosphate and sodium hexametaphosphate.

[0022] Preferably, the chemical composition of the toughening agent includes: CaO 40-58%, SiO 2 9-15%, Al 2 O 3 4-27%, SO 3 4-11%, and Fe 2 O 3 2.5-8.5%.

[0023] Preferably, the toughening agent has a specific surface area of ​​400-600m 2 / kg.

[0024] The present invention also relates to a method for preparing the high-performance cement-based composite material for repair and reinforcement engineering, which specifically comprises the following steps: 1) Weigh each raw material by weight, 2) Mix the compound cement, admixture, quartz sand, reinforcing agent and toughening agent evenly to obtain dry material. 3) Mix the nucleating agent and water evenly to obtain liquid material. 4) Slowly add the liquid material and mixed fibers into the dry material and mix evenly to obtain slurry. 5) Shape and cure the slurry.

[0025] Preferably, step 5) curing adopts standard curing. DETAILED DESCRIPTION

[0026] In order to characterize the technical effect of the present invention, cement-based repair materials were prepared and their performance was tested. During the test, the strength of each cement in the compound cement was 42.5, the water reducer adopted polycarboxylic acid water reducer, the defoamer adopted silicone defoamer, and the preparation process of ozone-modified PE fiber was as follows: the PE fiber was washed and dried, and placed in an ozone generator for oxidation treatment. The oxidation treatment temperature was 70°C, the ozone gas flux was 400mL / min, the ozone concentration was set at 20g / L, the oxidation treatment time was 30min, and then washed and dried again.

[0027] Example 1 The cement-based repair material is composed of the following raw materials in parts by weight: 110 parts of compound cement, 60 parts of admixture, 100 parts of quartz sand, 2 parts of mixed fiber, 3 parts of reinforcing agent, 2 parts of nucleating agent, 1.5 parts of toughening agent, and 40 parts of water. Compound cement is made by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of 2:3:1. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 25:8:6. The hybrid fiber is a mixture of ozone-modified PE fiber and PVA fiber in a mass ratio of 1:1. The reinforcing agent is a mixture of water reducing agent, defoaming agent, redispersible latex powder and lithium carbonate in a mass ratio of 2:3:4:2. The nucleating agent is a mixture of nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of 5:2:4. The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, quicklime and sodium tripolyphosphate in a mass ratio of 32:70:15:7:1.2.

[0028] After testing, the initial fluidity of the slurry is 240mm, the 2h flexural strength is 7.7MPa, the 60d flexural strength is 29.6MPa, the 2h compressive strength is 22.3MPa, the 60d compressive strength is 94.9MPa, and the 60d equivalent bending strength is 20.6N / mm 2 , 60d equivalent bending toughness is 361.4kJ / m 3 .

[0029] Example 2 The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of mixed fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water. Compound cement is made by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of 3:3:2. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 30:10:5. The hybrid fiber is made of ozone-modified PE fiber and PVA fiber in a mass ratio of 1:0.9. The enhancer is a mixture of water reducer, defoamer, redispersible latex powder and sodium nitrite in a mass ratio of 4:1:2:1. The nucleating agent is a mixture of nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of 3:1:4. The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium oxide and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0030] After testing, the initial fluidity of the slurry is 230mm, the 2h flexural strength is 8.0MPa, the 60d flexural strength is 30.8MPa, the 2h compressive strength is 21.6MPa, the 60d compressive strength is 90.1MPa, and the 60d equivalent bending strength is 21.8N / mm 2 , 60d equivalent bending toughness is 433.7kJ / m 3 .

[0031] Comparative Example 1 The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of mixed fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water. Compound cement is made by mixing ordinary Portland cement and sulphoaluminate cement in a mass ratio of 1:1. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 30:10:5. The hybrid fiber is made of ozone-modified PE fiber and PVA fiber in a mass ratio of 1:0.9. The enhancer is a mixture of water reducer, defoamer, redispersible latex powder and sodium nitrite in a mass ratio of 4:1:2:1. The nucleating agent is a mixture of nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of 3:1:4. The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium oxide and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0032] After testing, the initial fluidity of the slurry is 250mm, the 2h flexural strength is 6.5MPa, the 60d flexural strength is 24.9MPa, the 2h compressive strength is 13.8MPa, the 60d compressive strength is 80.5MPa, and the 60d equivalent bending strength is 15.7N / mm 2 , 60d equivalent bending toughness is 283.4kJ / m 3 .

[0033] Comparative Example 2 The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of mixed fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water. Compound cement is made by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of 3:3:2. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 30:10:5. The mixed fiber is made of PE fiber and PVA fiber in a mass ratio of 1:0.9. The enhancer is a mixture of water reducer, defoamer, redispersible latex powder and sodium nitrite in a mass ratio of 4:1:2:1. The nucleating agent is a mixture of nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of 3:1:4. The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium oxide and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0034] After testing, the initial fluidity of the slurry is 190mm, the 2h flexural strength is 4.6MPa, the 60d flexural strength is 23.2MPa, the 2h compressive strength is 15.1MPa, the 60d compressive strength is 73.6MPa, and the 60d equivalent bending strength is 10.5N / mm 2, 60d equivalent bending toughness is 256.4kJ / m 3 .

[0035] Comparative Example 3 The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of mixed fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water. Compound cement is made by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of 3:3:2. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 30:10:5. The hybrid fiber is made of ozone-modified PE fiber and PVA fiber in a mass ratio of 1:0.9. The reinforcing agent is a mixture of water reducing agent, defoaming agent, redispersible latex powder and sodium nitrite in a mass ratio of 4:1:2:1. The nucleating agent is a mixture of nano-CaCO3 and nano-graphene oxide in a mass ratio of 1:1. The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium oxide and sodium hexametaphosphate in a mass ratio of 34:60:20:8:2.

[0036] After testing, the initial fluidity of the slurry is 210mm, the 2h flexural strength is 5.4MPa, the 60d flexural strength is 22.7MPa, the 2h compressive strength is 10.6MPa, the 60d compressive strength is 73.0MPa, and the 60d equivalent bending strength is 12.4N / mm 2 , 60d equivalent bending toughness is 219.7kJ / m 3 .

[0037] Comparative Example 4 The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of mixed fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, 2 parts of toughening agent, and 40 parts of water. Compound cement is made by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of 3:3:2. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 30:10:5. The hybrid fiber is made of ozone-modified PE fiber and PVA fiber in a mass ratio of 1:0.9. The reinforcing agent is a mixture of water reducing agent, defoaming agent, redispersible latex powder and sodium nitrite in a mass ratio of 4:1:2:1. The nucleating agent is a mixture of nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of 3:1:4. The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum and sodium hexametaphosphate in a mass ratio of 54:70:3.

[0038] After testing, the initial fluidity of the slurry is 235mm, the 2h flexural strength is 4.3MPa, the 60d flexural strength is 23.2MPa, the 2h compressive strength is 10.5MPa, the 60d compressive strength is 62.4MPa, and the 60d equivalent bending strength is 12.7N / mm 2 , 60d equivalent bending toughness is 185.1kJ / m 3 .

[0039] Comparative Example 5 The cement-based repair material is composed of the following raw materials in parts by weight: 120 parts of compound cement, 50 parts of admixture, 110 parts of quartz sand, 3 parts of mixed fiber, 3 parts of reinforcing agent, 1.5 parts of nucleating agent, and 40 parts of water. Compound cement is made by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of 3:3:2. The admixture is a mixture of fly ash, mineral powder and silica fume in a mass ratio of 30:10:5. The mixed fiber is made of PP fiber and PVA fiber in a mass ratio of 1:0.9. The reinforcing agent is a mixture of water reducing agent, defoaming agent, redispersible latex powder and sodium nitrite in a mass ratio of 4:1:2:1. The nucleating agent is prepared by mixing nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of 3:1:4.

[0040] After testing, the initial fluidity of the slurry is 180mm, the 2h flexural strength is 1.6MPa, the 60d flexural strength is 19.7MPa, the 2h compressive strength is 3.1MPa, the 60d compressive strength is 60.6MPa, and the 60d equivalent bending strength is 4.6N / mm 2 , 60d equivalent bending toughness is 120.3kJ / m 3 .

[0041] It can be seen from the technical effects of the embodiments that the cement-based composite material of the present invention has a high-ductility concrete effect, and has the characteristics of good fluidity, rapid hardening and high strength, and can be used in repair and reinforcement projects.

[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-performance cement-based composite material for repair and reinforcement engineering, characterized in that: The invention is composed of the following raw materials in parts by weight: 100-120 parts of compound cement, 30-60 parts of admixture, 90-120 parts of quartz sand, 1-3 parts of mixed fiber, 2-5 parts of reinforcing agent, 1-3 parts of nucleating agent, 1-2 parts of toughening agent, and 38-42 parts of water. The composite cement is prepared by mixing silicate cement, sulphoaluminate cement and aluminate cement in a mass ratio of (2-4):(1-4):(1-2). The admixture is prepared by mixing fly ash, mineral powder and silica fume in a mass ratio of (10-30):(8-12):(5-7). The hybrid fiber is formed by mixing ozone-modified PE fiber and PVA fiber in a mass ratio of 1:(0.9-1.2). The reinforcing agent is prepared by mixing a water reducing agent, a defoaming agent, a redispersible latex powder and an early strength agent in a mass ratio of (2-4):(1-4):(1-4):(1-2). The nucleating agent is prepared by mixing nano-SiO2, nano-CaCO3 and nano-graphene oxide in a mass ratio of (2-5):(1-3):(3-5). The toughening agent is prepared by mixing and grinding calcium aluminate clinker, gypsum, CSA expansion agent, calcium raw material and dispersant in a mass ratio of (30-40):(55-75):(10-22):(3-15):(1-2.5).

2. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 1, characterized in that: The strength grade of each cement in the composite cement is ≥42.

5.

3. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 1, characterized in that: The ozone-modified PE fiber preparation process comprises: washing and drying the PE fiber, placing the PE fiber in an ozone generator for oxidation treatment, and washing and drying the fiber again to obtain the ozone-modified PE fiber.

4. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 3, characterized in that: The oxidation treatment temperature is 60-80° C., the ozone gas flux is 200-500 mL / min, the ozone concentration is set at 19-22 g / L, and the oxidation treatment time is 25-40 min.

5. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 3, characterized in that: The PE fiber length is 6-18 mm.

6. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, the defoamer is an organosilicon defoamer, and the early strength agent is at least one of tartaric acid, lithium carbonate, and sodium nitrite.

7. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 1, characterized in that: The gypsum is at least one of anhydrite, dihydrate gypsum and hemihydrate gypsum, the calcium raw material is at least one of calcium oxide, quicklime and slaked lime, and the dispersant is at least one of sodium tripolyphosphate and sodium hexametaphosphate.

8. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 1, characterized in that: The chemical composition of the toughening agent includes: CaO 40-58%, SiO 2 9-15%, Al 2 O 3 4-27%, SO 3 4-11%, and Fe 2 O 3 2.5-8.5%.

9. The high-performance cement-based composite material for repair and reinforcement engineering according to claim 1, characterized in that: The specific surface area of ​​the toughening agent is 400-600m 2 / kg.

10. The method for preparing a high-performance cement-based composite material for repair and reinforcement engineering according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Mix the compound cement, admixture, quartz sand, reinforcing agent and toughening agent evenly to obtain dry material. 3) Mix the nucleating agent and water evenly to obtain liquid material. 4) Slowly add the liquid material and mixed fibers into the dry material and mix evenly to obtain slurry. 5) Shape and cure the slurry.

Citation Information

Patent Citations

  • Self-growing nano ettringite fiber toughening agent as well as preparation method and application thereof

    CN114044643A

  • Self-growing nano ettringite fiber toughened concrete and preparation method thereof

    CN115872707A

  • Self-repairing steam-cured concrete material and preparation method thereof

    CN118206352A

  • Ultrahigh-performance repairing grouting material for underwater construction as well as preparation method and application thereof

    CN118955064A

  • Quick-hardening cement-based bridge deck pavement material and preparation method thereof

    CN119409463A

Cited By

  • Heat preservation and insulation coating material as well as preparation method and application thereof

    CN120534023A